Health Outcomes from Multi-Drug-resistant Salmonella Infections in High-Income Countries: A Systematic Review and Meta-Analysis. (4th October 2017) - Parisi, Andrea; Crump, John A; Kirk, Martyn; Glass, Kathryn; Howden, Benjamin; Gray, Darren; Furuya-Kanamori, Luis; Vilkins, Samantha
Abstract: Background: Salmonella is a leading cause of foodborne enterocolitis worldwide. Nontyphoidal Salmonella (NTS) infections that are Multi-Drug-resistant (MDR) (non-susceptible to ≥1 agent in ≥3 antimicrobial categories) may result in more severe health outcomes, although these effects have not been systematically examined. We conducted a systematic review and meta-analysis to examine impacts of MDR NTS on disease outcomes in high-income settings. Methods: We systematically reviewed the literature from scientific databases, including PubMed, Scopus and grey literature sources, using Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. We included case–control studies, cohorts, outbreaks, and theses, imposing no language restriction. We included only publications from 1 January 1990 through 15 September 2016 from high-income countries as classified by the World Bank, and extracted data on duration of illness, hospitalization, morbidity and mortality of MDR and susceptible NTS infections. Results: After we removed duplicates, the initial search revealed 4 258 articles. After further screening, we identified 16 eligible studies for the systematic review, but due to inconsistency in the compared groups, only 9 of these were included in the meta-analysis. NTS serotypes differed among the reported studies but serotypes Typhimurium, Enteritidis, Newport, and Heidelberg were the most often reported MDR pathogens. Salmonella infections that were MDR were associated with excess bloodstream infections (OR 1·73; 95% CI 1·32–2·27), excess hospitalizations (OR 2·51; 95% CI 1·38–4·58), and higher mortality (OR 3·54; 95% CI 1·10–11·40). Conclusion: The results of this meta-analysis suggest that MDR NTS infections have more serious health outcomes compared with susceptible isolates. With the emergence of MDR Salmonella strains in high-income countries, it is crucial to restrict the use of antimicrobials in animals and humans, and intervene to prevent foodborne infections. Disclosures: All authors: No reported disclosures.